2007
DOI: 10.1097/mao.0b013e318159e74f
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Midbrain Implant

Abstract: The histomorphologic effects and extent of neuronal damage observed for our AMI array are similar to those of other neural implants currently and safely used in humans. The minimal tissue damage surrounding the implanted array is encouraging with regard to the safety of the array for human use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

5
5

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 36 publications
1
9
0
1
Order By: Relevance
“…The development of the AMI was based upon hypotheses that poor outcomes with the auditory brainstem implant (ABI) were related to tumor or surgical damage to important cells in the cochlear nucleus (CN) (Colletti 2006), and the theoretical ability to access frequency layers in the IC. Early studies with the first recipients of the AMI device (Lenarz et al 2006a,b, 2007; Lim et al 2007, 2008a,b, 2009) showed that patients gained benefits for speech understanding, when combined with lip-reading, that were similar to those generally observed for patients using ABIs for stimulation of the CN (McCreery 2008; Schwartz et al 2008; Colletti et al 2009). Although these outcomes are poorer than expected for CI users, it is possible that performance could be improved with development of more appropriate electrode array designs and processing strategies that are optimized for stimulation of the IC.…”
Section: Introductionmentioning
confidence: 74%
“…The development of the AMI was based upon hypotheses that poor outcomes with the auditory brainstem implant (ABI) were related to tumor or surgical damage to important cells in the cochlear nucleus (CN) (Colletti 2006), and the theoretical ability to access frequency layers in the IC. Early studies with the first recipients of the AMI device (Lenarz et al 2006a,b, 2007; Lim et al 2007, 2008a,b, 2009) showed that patients gained benefits for speech understanding, when combined with lip-reading, that were similar to those generally observed for patients using ABIs for stimulation of the CN (McCreery 2008; Schwartz et al 2008; Colletti et al 2009). Although these outcomes are poorer than expected for CI users, it is possible that performance could be improved with development of more appropriate electrode array designs and processing strategies that are optimized for stimulation of the IC.…”
Section: Introductionmentioning
confidence: 74%
“…In humans, the inferior colliculus is surgically accessible (Kaku et al 1999;Simmons et al 1964). Similar to the ABI surgery in NF2 patients, AMI implantation can be performed after tumor removal with minimal added risk using a lateral supracerebellar infratentorial approach performed through a lateral suboccipital craniotomy (semisitting position) (Lenarz et al 2003(Lenarz et al , 2004. Using this approach, an AMI array can be inserted along the tonotopic gradient of the ICC.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the clinical trial, these researchers and clinicians had shown that ICC stimulation achieves low threshold and frequency-specific auditory activation in animals that was better or comparable to CI stimulation (Lenarz et al, 2006a; Lim et al, 2006). They also showed in a cat model that long-term implantation and stimulation of the AMI device was safe without any major side effects and induced minimal tissue damage that was comparable to other clinically approved brain implants (Lenarz et al, 2007). In terms of sound coding, multiple studies have shown that ICC neurons are capable of following the temporal modulations of acoustic stimuli up to or beyond 100 Hz and the ICC has a well-defined tonotopic organization (Geniec et al, 1971; Joris et al, 2004; Langner et al, 2002; Oliver, 2005; Rees et al, 2005; Schreiner et al, 1997).…”
Section: Findings From the First Clinical Trialmentioning
confidence: 79%